2016
DOI: 10.2196/resprot.4354
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of a Tailored eHealth Service for Informal Caregivers and Professionals in the Dementia Treatment and Care Setting: The eHealthMonitor Dementia Portal

Abstract: BackgroundThe European eHealthMonitor project (eHM) developed a user-sensitive and interactive Web portal for the dementia care setting called the eHM Dementia Portal (eHM-DP). It aims to provide targeted support for informal caregivers of persons with dementia and professionals.ObjectiveThe objective of this study was to assess the usefulness and impact of the eHM-DP service in the dementia care setting from two user perspectives: informal caregivers and professionals.MethodsThe evaluation study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 58 publications
2
74
0
1
Order By: Relevance
“…) should be resolved, whereas consistent linkage between clinical research and clinical practice will also help to significantly reduce the need for double data entry, which is currently often common practice. Specific attention should be paid to the fact that different professionals and organizations that participate in the patient's journey have different priorities (Schaller et al 2016). Mass scale: For long-term data collection of health-related data, individual participation at a mass scale is important.…”
Section: Conclusion and Guidelines For Future Developmentmentioning
confidence: 99%
“…) should be resolved, whereas consistent linkage between clinical research and clinical practice will also help to significantly reduce the need for double data entry, which is currently often common practice. Specific attention should be paid to the fact that different professionals and organizations that participate in the patient's journey have different priorities (Schaller et al 2016). Mass scale: For long-term data collection of health-related data, individual participation at a mass scale is important.…”
Section: Conclusion and Guidelines For Future Developmentmentioning
confidence: 99%
“…A German pilot study reported on the development of a tailored e-health service for caregivers/carers of people living with dementia and HSCPs. 186,187 The aim of the tool was to facilitate communication between HCPs and informal carers and to empower the carers. Although not aimed at SDM, the intervention included an element related to preparation for doctors' visits.…”
Section: Family-centred Approachesmentioning
confidence: 99%
“…Az egyre intenzívebb kutatások során számos olyan terület körvonalazódott, melyben az IKT-megközelítés segíthet az időseknek, úgymint az önállóság biztosítása, az elesés rizikójának mérséklése, a krónikus testi és men-tális betegségek (például a dementia vagy a depresszió) negatív következményeinek enyhítése és a gyógyszeres kezeléssel való együttműködés biztosítása, valamint a szociális izoláció oldása és az életminőség javítása [8,13]. Az idősek körében végzett, a különböző információs és kommunikációs eszközök hatását felmérő vizsgálatokat, randomizált-kontrollált vizsgálatokat (RKV) és metaanalíziseket a 3. táblázatban foglaltuk össze [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Infokommunikációs Eszközök Alkalmazása a Dementiával éLők Kounclassified